Effect of Blood Group on Ultrahigh Frequency Auditory Sensitivity - Prabhu, Prashanth; Chandrashekhar, Akhila; Cariappa, Janani; Ghosh, Nayanika (International Archives of Otorhinolaryngology, 2018)
Introduction Individuals with blood group O are reported to have reduced otoacoustic emissions (OAEs) compared with individuals with different blood groups.Objective The present study attempted to determine if the blood group has any effect on high-frequency auditory sensitivity using ultrahigh-frequency audiometry and ultrahigh-frequency distortion product otoacoustic emissions (DPOAEs).Methods High-frequency thresholds and high-frequency DPOAEs were measured in 60 individuals with normal hearing and different blood groups.Results The results of the study showed that there was a significant reduction in DPOAE amplitude for individuals with blood group O compared with individuals with other blood groups. However, there was no significant difference in ultrahigh-frequency thresholds across the blood groups.Conclusion This reduction in OAE amplitude may be attributed to a lower number of healthy outer hair cells in individuals with blood group O. Further studies on larger groups of individuals are essential for a better generalization of the results.
Keywords: noise-induced hearing loss; ABO blood group system; audiometry